Improved survival of chimeric antigen receptor‐engineered T (CAR‐T) and tumor‐specific T cells caused by anti‐programmed cell death protein 1 single‐chain variable fragment‐producing CAR‐T cells. Issue 10 (17th September 2019) - Nakajima, Masao; Sakoda, Yukimi; Adachi, Keishi; Nagano, Hiroaki; Tamada, Koji
Abstract: Chimeric antigen receptor‐engineered T (CAR‐T)‐cell therapy holds significant promise for the treatment of hematological malignancies, especially for B‐cell leukemia and lymphoma. However, its efficacy against non‐hematological malignancies has been limited as a result of several biological problems characteristic of the tumor microenvironment of solid tumors. One of the main hurdles is the heterogeneous nature of tumor‐associated antigens (TAA) expressed in solid tumors. Another hurdle is the inefficient activation and limited persistence of CAR‐T cells, mainly as a result of T‐cell exhaustion caused by immunosuppressive factors in the tumor microenvironment. In the present study, to address these problems, we engineered CAR‐T cells to produce antagonistic anti‐programmed cell death protein 1 (PD‐1) single‐chain variable fragment (scFv), by which PD‐1‐dependent inhibitory signals in CAR‐T cells and adjacent tumor‐specific non‐CAR‐T cells are attenuated. In mouse solid tumor models, PD‐1 scFv‐producing CAR‐T cells induced potent therapeutic effects superior to those of conventional CAR‐T cells, along with a significant reduction of apoptotic cell death not only in CAR‐T cells themselves but also in TAA‐specific T cells in the tumor tissue. In addition, the treatment with anti‐PD‐1 scFv‐producing CAR‐T cells resulted in an increased concentration of PD‐1 scFv in tumor tissue but not in sera, suggesting an induction of less severe systemic immune‐related adverse events. Hence, the present study developed anti‐PD‐1 scFv‐producing CAR‐T cell technology and explored its cellular mechanisms underlying potent antitumor efficacy. Abstract : We developed CAR‐T cells producing anti‐PD‐1 scFv to attenuate PD‐1 inhibitory signals and showed their potent therapeutic efficacy in mouse solid tumor models. Anti‐PD‐1 scFv‐producing CAR‐T cells decreased apoptotic cell death of CAR‐T cells and endogenous tumor‐specific T cells in association with upregulation of Bcl‐xL. To the best of our knowledge, this is the first study to explore the detailed mechanisms of how PD‐1 blocker‐producing CAR‐T cells mediate antitumor efficacy in solid tumors.